Pengaruh Penerapan Sistem Manajemen Sumber Daya Perusahaan (ERP) dalam Meningkatkan Kinerja Manajemen Rantai Pasok (SCM) PT. Unilever Indonesia - Yulfis Yulfis; Defen Defen; Deviana Lie; Jason Jason; Jesty Jesty; Jolin Jolin (Public Service and Governance Journal, 2023)
As we all know, employees must be able to think logically and engage with their environment. Work is not only dependent on or prioritized by machines or technical equipment. Recognizing the importance of supply chain management in every company and using a capable Enterprise Resource Management system or often known as an Enterprise Resource System (ERP) to solve problems and increase revenue in improving the performance of existing supply chain management in a company. Therefore, we will use PT. Unilever Indonesia to research this research topic. As PT. Unilever Indonesia sales of various consumer products, including culinary spices, body care products, cosmetics and toiletries; which means PT. Unilever must have a stable supply chain.